Risk factors associated with heel pressure ulcer development in adult population: A systematic literature review. Issue 1 (February 2022) - Dube, Alisen; Sidambe, Viola; Verdon, Amy; Phillips, Eloise; Jones, Sarahjane; Lintern, Maxine; Radford, Mark
Abstract: Aims: The main aim of this systematic literature review was to identify risk factors for development of heel pressure ulcers and quantify their effect. Background: Pressure ulcers remain one of the key patient safety challenges across all health care settings and heels are the second most common site for developing pressure ulcers after the sacrum. Design: Quantitative systematic review. Methods: Data sources: Electronic databases were searched for studies published between 1809 to March 2020 using keywords, Medical Subject Headings, and other index terms, as well as combinations of these terms and appropriate synonyms. Study eligibility criteria: Previous systematic literature reviews, cohort, case control and cross-sectional studies investigating risk factors for developing heel pressure ulcers. Only articles published in English were reviewed with no restrictions on date of publication. Participants: patients aged 18 years and above in any care setting. Study selection, data extraction, risk of bias and quality assessment were completed by two independent reviewers. Disagreements were resolved by discussion. Results: Thirteen studies met the eligibility criteria and several potential risk factors were identified. However, eligible studies were mainly moderate to low quality except for three high quality studies. Conclusions: There is a paucity of high quality evidence to identify risk factors associated with heel pressure ulcer development. Immobility, diabetes, vascular disease, impaired nutrition, perfusion issues, mechanical ventilation, surgery, and Braden subscales were identified as potential risk factors for developing heel pressure ulcers however, further well-designed studies are required to elucidate these factors. Other risk factors may also exist and require further investigation. Prospero id: PROSPERO International prospective register of systematic reviews: CRD42017071459 . Implications for practice and future research: Heels remain the second most common site for developing pressure ulcers. Estimated incidence and prevalence rates remain high (least 17% and 11% respectively). Current HPU preventative interventions require further improvement in order to reduce the incidence rates and prevent harm. This is the first systematic literature review of risk factors associated with development of HPUs in adult population. Several potential risk factors for developing HPU have been identified in this review. Only three studies involving heterogenous populations, were rated as high quality in this review. There is a lack of high-quality studies to inform evidence-based practise, further research is required to inform practice.